Math virtual assistant

Calculators Topics Go Premium About Snapxam
ENGESP

Step-by-step Solution

Solve the equation $x^2-3x-4=\left(x+1\right)\left(x-4\right)$

Go!
1
2
3
4
5
6
7
8
9
0
x
y
(◻)
◻/◻
÷
2

e
π
ln
log
log
lim
d/dx
Dx
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Answer

true

Step-by-step explanation

Problem to solve:

$x^2-3x-4=\left(x+1\right)\left(x-4\right)$
1

Grouping all terms to the left side of the equation

$x^2-3x-4-\left(x+1\right)\left(x-4\right)=0$
2

The product of two binomials of the form $(x+a)(x+b)$ is equal to the product of the first terms of the binomials, plus the algebraic sum of the second terms by the common term of the binomials, plus the product of the second terms of the binomials. In other words: $(x+a)(x+b)=x^2+(a+b)x+ab$

$x^2-3x-4-\left(x^2+\left(1-4\right)x+1-4\right)=0$

Unlock this step-by-step solution!

Answer

true
$x^2-3x-4=\left(x+1\right)\left(x-4\right)$

Main topic:

Equations

Time to solve it:

~ 0.04 seconds